PENERAPAN MODEL GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA DI KELAS IV SDN 018 LANGGINI KABUPATEN KAMPAR - Yenni Fitra Surya (JURNAL HANDAYANI PGSD FIP UNIMED, 2017)
Abstract: Application of Model Group Investigation To Improve Student Learning Outcomes Science Class IV SDN 018 Langgini Kampar: This research is motivated low activity and learning outcomes of students at SDN 018 IPA Langgini. Learning science which is always dominated by the teacher so that science subjects are considered by students as subjects of memorization. This type of research is a classroom action research (PTK) are conducted in two cycles. Each cycle contains the main points of planning, implementation, observation and reflection. This study was conducted in class IV SDN 018 Langgini Kampar, with the number of students 33 people. Based on the results of the discussion and analysis as described in chapter IV can be concluded that through the application of the model group investigation IPA can improve learning outcomes of students. The increased activity is due to the teachers of teachers are already familiar with the model group investigation, Student learning outcomes before treatment by an average of 50% with less category, then the cycle I get enough category with 63.6% students who completed 21 students. Cycle II earn on average 84.5% of both categories with students who completed 28 students. Keywords : Model Group Investigation, Learning Outcomes, IPA. Abstrak: Penerapan Model Group Investigation Untuk Meningkatkan Hasil Belajar IPA Siswa Kelas IV SDN 018 Langgini Kabupaten Kampar:  Penelitian ini dilatarbelakangi rendahnya aktivitas dan hasil belajar IPA siswa di SDN 018 Langgini. Jenis penelitian ini merupakan penelitian tindakan kelas (PTK) yang dilaksanakan dalam dua siklus. Penelitian ini dilaksanakan dikelas IV SDN 018 Langgini Kabupaten Kampar, dengan jumlah siswa 33 orang. Berdasarkan hasil pembahasan dan dapat disimpulkan bahwa melalui penerapan model group investigation dapat meningkatkan hasil belajar IPA siswa. Hasil belajar siswa sebelum tindakan dengan rata-rata sebesar 50% dengan kategori kurang, kemudian pada siklus I mendapatkan 63,6% kategori cukup dengan siswa yang tuntas 21 siswa. Siklus II mendapatkan rata-rata 84,5% kategori baik dengan siswa yang tuntas 28 siswa. Kata kunci : Model Group Investigation, Hasil Belajar, IPA